The Imperative of Integrating Artificial Intelligence into Elementary Social Studies Education - Grubaugh, Steven; Levitt, Greg; Lam, Ivana (Technium Social Sciences Journal, 2026)
Elementary students already live in an AI mediated information environment. Search, recommendation systems, and generative tools shape what students read, watch, and believe, often without students realizing that an algorithm is curating the experience. This article argues that elementary Social Studies is an especially strong and practical starting point for AI literacy because it already teaches how communities make decisions, how evidence is used, and how people should treat one another. We offer a classroom ready approach that reduces plagiarism risk by emphasizing original teacher authored routines and locally grounded tasks: a grade band progression for AI civic reasoning, a 10 minute weekly VERIFY routine for evaluating claims, and three project vignettes that can be implemented with typical time and technology constraints. We also clarify limits and safeguards, including age appropriate privacy practices and when to avoid student use of general purpose chatbots. The goal is not to turn children into computer scientists. The goal is to build early habits of evidence, judgment, and civic responsibility that help students learn well today and participate wisely in a democracy tomorrow.